Konseptualisasi Isu Privasi dan Keamanan pada Knowledge Management System (KMS) Perusahaan - Satibi, Iswanda F.; Atmi, Ragil Tri (UI Scholars Hub, 2019)
This article describes the distinct of privacy and security issues that are simultaneously operant in the KMS practices. It identifies several perceptions of privacy and security issues in the company’s KMS settings. By studying the perspective, authors provide a conceptual directions to the fog of misunderstandings around privacy and security in company’s KMS settings. An exploratory sequential mixed method research design was adopted. A questionnaire survey was administered by authors personally handing to KM staff in three companies, followed by semi-structure interviews with four KM staff. The findings of this study show that the employees were aware of the importance of KMS in the companies, and hence had a high awareness of personal information privacy and security issues. In short, the distinct perspective of privacy issue in companies can be distinguished from organizational layer of KMS through three dimensions; confidentiality, trust, and behavior. While the security aspects in KMS have complied with ICT layer which constructed by legal framework and KMS architecture.